A bibliometric analysis of reverse logistics research (1992-2015) and opportunities for future research. Issue 8 (4th September 2017) - Wang, Jian-Jun; Chen, Haozhe; Rogers, Dale S.; Ellram, Lisa M.; Grawe, Scott J.
Abstract : Purpose: Interest in reverse logistics (RL) as a critical component of supply chain management (SCM) is gaining more traction with both practitioners and academics. Because of RL's growing strategic importance, it is imperative to conduct a timely and comprehensive literature review and to identify associated opportunities for future research. The paper aims to discuss these issues. Design/methodology/approach: In this paper, the researchers conduct an extensive bibliometric analysis of published academic articles on RL for the period of 1992-2015. Specifically, the CiteSpace software is utilized to conduct document co-citation analysis and burst detection analysis on 912 selected RL articles and their 22, 642 references. Findings: This research identifies the most influential RL research publications/citations in each of the five periods and their research contribution. Using co-citation analysis, the authors are able to identify and illustrate major research themes, knowledge groups, and future research opportunities in the RL field. Originality/value: In contrast to existing literature review studies in the logistics field, the study uses impact factor as a key article selection criterion. The influential articles identified in this process well represent the core literature and RL body of knowledge and have important implications for future research.